Effect of the Nipple-Excising Breast-Conserving Therapy in Female Breast Cancer: A Competing Risk Analysis and Propensity Score Matching Analysis of Results Based on the SEER Database - Li, Shouyu; Zhao, Yuting; Yan, Lutong; Yang, Zejian; Qiu, Pei; Chen, Heyan; Zhou, Yudong; Niu, Ligang; Yan, Yu; Zhang, Wei; Zhang, Huimin; He, Jianjun; et al. (Frontiers in Oncology, 2022)
IMPORTANCE Due to the lack of randomized controlled trial, the effectiveness and oncological safety of nipple-excising breast-conserving surgery (NE-BCS) for female breast cancer (FBC) remains unclear .OBJECTIVE To explore and investigate the prognostic value of NE-BCS versus nipple-sparing breast-conserving surgery (NS-BCS) for patients with early FBC.DESIGN,SETTING,AND PARTICIPANTS In this cohort study, data between NE-BCS and NS-BCS groups on 276,661 patients diagnosed with TNM stage 0-III FBC between 1998 and 2015 were retrieved from the Surveillance, Epidemiology, and End Results database. Propensity score matching analysis Kaplane-Meier, X-tile, Cox proportional hazards model and competing risk model were performed to evaluate the effectiveness and oncological safety of NE-BCS and NS-BCS groups.RESULTS A total of 1731 (0.63%) patients received NE-BCS (NE-BCS group) and 274930 (99.37%) patients received NS-BCS (NS-BCS group) and 44070 subjects died after a median follow-up time of 77 months (ranging from 1 to 227 months). In the PSM cohort, surgical procedures, were found to be independent prognostic factor affecting overall survival (OS) and deaths from causes unrelated to breast cancer (OCSD). When compared with subjects in the NS-BCS group, patients in NE-BCS group had similar BCSS (HR:1.15,95%CI: 0.88-1.52, P=0.30), but worse OS (HR:1.24, 95% CI:1.06-1.45, P=0.0078) and improve OCSD (HR:0.822, 95% CI: 0.676-0.99, P=0.048 < 0.05). Her-2-negative tumors in Her-2 status was only borderline corrected with OCSD (HR:0.543, 95% CI:0.2956-0.999, P= 0.05) rather than breast cancer-specific death (BCSD) (HR:1.222 ,95% CI:0.2956-0.999, P= 0.64 > 0.05). CONCLUSIONS AND RELEVANCE Our study demonstrated that nipple-excising breast-conserving surgery (NE-BCS) is one oncologically safe and effective surgical treatment and can be widely recommended in clinics for wemen with non-metastatic breast cancer.